1995
DOI: 10.1021/j100013a030
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Distorted WO4 in the Oxidative Coupling of Methane on Supported Tungsten Oxide Catalysts

Abstract: Raman spectroscopy has been applied to characterize the W -0 tetrahedron on supported tungsten oxide catalysts. The existence of distorted WO4 has an important influence on its catalytic properties. When Na+ ion is added to WO3/SiO2 catalyst, the distorted W04 tetrahedron forms, and the selectivity to CZ hydrocarbons significantly increases. The W -0 bond order may be correlated with the selectivity to CZ hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 5 publications
(5 reference statements)
3
47
0
Order By: Relevance
“…It is evident from the data collected that the Na 2 WO 4 and Mn 2 O 3 are not stabilized on the MgOsupported catalyst, and this is likely the reason for its poor performance. The importance of a stable Na 2 WO 4 phase has been emphasized in the literature, as a distorted WO4 2-tetrahedron stabilized by -cristobalite SiO 2 and Na + may be part of the active site[9,20]. This is supported in the current study by the identification of the H 4 Na 2 WO 6 phase.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…It is evident from the data collected that the Na 2 WO 4 and Mn 2 O 3 are not stabilized on the MgOsupported catalyst, and this is likely the reason for its poor performance. The importance of a stable Na 2 WO 4 phase has been emphasized in the literature, as a distorted WO4 2-tetrahedron stabilized by -cristobalite SiO 2 and Na + may be part of the active site[9,20]. This is supported in the current study by the identification of the H 4 Na 2 WO 6 phase.…”
supporting
confidence: 77%
“…Evidence suggests that the WO 4 2-tetrahedron is distorted upon interaction with the SiO 2 support [20], and it is possible that the distorted WO 4 2-tetrahedron has the correct symmetry for interaction with the methane molecule [9], and may be sufficiently, or more, reactive due to the distortion. Furthermore, the W 6+ can easily accept an electron to form W 5+ upon hydrogen abstraction from methane.…”
Section: Active Site Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Na 2 WO 4 /SiO 2 system, the reconstruction of surface WO 4 tetrahedral units into a structure containing a W=O and three W-O-Si surface bonds was responsible for the OCM reaction via a redox mechanism [22,23], and molecular oxygen is activated by an F-center to produce lattice oxygen O 2- [24]. Cobalt catalysts supported on alumina can catalyze methane partial oxidation [25], as well as CO 2 reforming of methane [26].…”
Section: The Dual-catalytic Performances Of Na 2 Wo 4 /Co-mn/siomentioning
confidence: 99%
“…This surface cluster compound formed by the reconstruction of surface tetrahedral WO 4 might constitute to the active phase for OCM on MnNa 2 WO 4 /SiO 2 catalyst. Wu et al [26] suggested that the shortest W-O bond of the distorted WO 4 tetrahedron might be the active phase for OCM reaction, while the catalyst with W-O octahedral coordinated structure was inactive for effectively converting CH 4 to C 2 hydrocarbons. They proposed that the octahedral structure was changed into a distorted tetrahedron due to the presence of Na + , and the WO 4 tetrahedron on 5% Na 2 WO 4 /SiO 2 catalyst distorted to some extent by the interaction of Na 2 WO 4 with the silica support.…”
Section: Introductionmentioning
confidence: 99%